Mitochondrial and Nuclear DNA in Patients with Severe Polytrauma - M. Sh Khubutia; A. K Shabanov; M. V Skulachev; G. V, Bulava; I. M Savchenko; O. A. Grebenchikov; A. A. Sergeev; D. B. Zorov; R. A. Zinovkin (Общая реаниматология)
The components of mitochondria from the cells damaged by injury are a key component for the development of systemic inflammatory response syndrome (SIRS) under aseptic conditions. At the same time, there is a significant increase in the plasma level of mitochondrial DNA (mtDNA), which may be a prognostic marker for infectious complications in patients with severe polytrauma. Objective: to study the time course of changes in the serum levels of mtDNA and nuclear DNA (nDNA) in healthy individuals and patients with polytrauma and to reveal its possible association with the development of infectious pulmonary complications and with mortality. Subjects and methods. Seven healthy volunteers and 25 polytrauma with polytrauma of a mean injury severity score (ISS) of 40.2±9.2. Sixteen (64%) patients developed purulent tracheobronchitis and pneumonia; 5 (20%) patients died. The amount of mtDNA and nDNA was determined within the first at 12 and 24 hours, then on days 3 and 5—7 after injury by the authors’ modified procedure using as the exogenous control of a circular DNA molecule. The content of mtDNA and nDNA was expressed as absolute values, by taking the arithmetic mean values as 100% for the volunteers. Results. There was a more than 2.5-fold increase in mtDNA levels in dead patients as compared to survivors (p<0.05); the differences in nDMA levels were insignificant (p=0.1). Within the first 12 hours, the mean mtDNA level in patients with pneumonia was 34 times greater than the reference values and continued to rise in the following 12 hours whereas in those without pneumonia, it was only 17 times higher with its further decrease in the comparable time periods. In the first 12 hours, nDNA was increased in both groups, but 24 hours after injury it was 2555 times more than the reference value only in patients with pneumonia whereas it was decreased 3-fold in those without this condition. Conclusion. This paper is the first to describe the time course of changes in the amount of mtDNA and nDNA with the new modification of using an external control DNA molecule in the serum of patients with polytrauma who developed infectious pulmonary complications and in patients without the latter. The findings point to the fact that it is advisable to measure mtDNA and nDNA in patients with polytrauma within the first 24 hours of hospital admission for the prediction of the development of infectious bronchopulmonary complications and for timely etiotropic therapy and that it is promising to conduct further investigations in this area. Key words: polytrauma, infectious complications, pneumonia, mitochondrial DNA, nuclear DNA, PAMS, DAMPs, CCBO, predictor, mortality, injury severity score, mechanical ventilation.